2012
DOI: 10.1038/hdy.2012.109
|View full text |Cite
|
Sign up to set email alerts
|

Porcine colonization of the Americas: a 60k SNP story

Abstract: The pig, Sus scrofa, is a foreign species to the American continent. Although pigs originally introduced in the Americas should be related to those from the Iberian Peninsula and Canary islands, the phylogeny of current creole pigs that now populate the continent is likely to be very complex. Because of the extreme climates that America harbors, these populations also provide a unique example of a fast evolutionary phenomenon of adaptation. Here, we provide a genome wide study of these issues by genotyping, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
88
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 39 publications
11
88
1
3
Order By: Relevance
“…Population structures determined in wild boars and domestic pigs using the high-density genotyping panel (for example, Ai et al, 2013, Burgos-Paz et al, 2013, Wilkinson et al, 2013 confirm previous findings primarily based on mitochondrial (Figure 2) and microsatellite markers, evidencing a strong differentiation between Asian and European individuals. Moreover, the presence of admixture from Asian breeds into commercial European breeds and vice versa was also obvious.…”
Section: Moving Towards An Autosomal and Paternal Marker-based Definisupporting
confidence: 70%
See 1 more Smart Citation
“…Population structures determined in wild boars and domestic pigs using the high-density genotyping panel (for example, Ai et al, 2013, Burgos-Paz et al, 2013, Wilkinson et al, 2013 confirm previous findings primarily based on mitochondrial (Figure 2) and microsatellite markers, evidencing a strong differentiation between Asian and European individuals. Moreover, the presence of admixture from Asian breeds into commercial European breeds and vice versa was also obvious.…”
Section: Moving Towards An Autosomal and Paternal Marker-based Definisupporting
confidence: 70%
“…This is the case for the 60K SNP panel (Ramos et al, 2009), which was built on the basis of sequence variation found in a pool of six populations (Duroc, Landrace, Pietrain and Large White breeds and a wild boar pool containing mainly European and a few Japanese samples). Ascertainment bias has been observed in the 60K SNP panel, especially in nonEuropean pig populations Burgos-Paz et al, 2013). Population structure analyses based on this panel are restricted to the detection of differences exclusively targeting ascertained SNPs.…”
Section: Moving Towards An Autosomal and Paternal Marker-based Definimentioning
confidence: 99%
“…Inicialmente llegaron a las Antillas y desde allí emigraron al resto del continente. Colón trajo cerdos en su segundo viaje (Burgos et al, 2013). Años después, y por exigencia de Carlos V, la excursión de Rodrigo Bastidas que salió de la Española y fundó Santa Marta en 1525, trajo 300 cerdos (Peña y Mora, 1977 El ADN se extrajo de las muestras mediante una modificación al protocolo descrito por Sambrook y Russell (2001), a partir del bulbo piloso, mediante digestión de proteínas con la enzima Proteinasa K y una purificación con fenol-cloroformo.…”
Section: Introductionunclassified
“…Los cerdos domésticos del continente americano tienen su origen en los cerdos ibéricos traídos por Colón en su segundo viaje (1). Años más tarde por imposición de Carlos V, la expedición de Rodrigo Bastidas que partió de la española y fundó a Santa Marta en 1525, trajo 300 cerdos (2).…”
Section: Introductionunclassified
“…The snout is cylindrical in shape with a bulky edge; hairless and smooth; the nostrils are small and its eyes have round pupils. Domestic pigs in the Americas have their origin in the Iberian pigs brought by Columbus on his second voyage (1). Years later by imposition of Carlos V, the expedition of Rodrigo Bastidas who left La Española and founded Santa Marta in 1525, brought 300 pigs (2).…”
Section: Introductionmentioning
confidence: 99%